2018
DOI: 10.1007/s00408-018-0101-2
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D Metabolism Gene Polymorphisms and Risk of Tunisian Adults’ Asthma

Abstract: We found that rs12794714 and rs10877012 SNPs were associated with asthma risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
3
2
0
1
Order By: Relevance
“…Our results were consistent with Li et al and Zhang et al findings . In contrary, a study carried out on Tunisian population denied any correlation between rs4588 variant and bronchial asthma . Another case‐control study carried out among 6‐year‐old Hispanic children showed that rs4588 and rs7041 GC variants are significant determinants of asthma risk in children …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results were consistent with Li et al and Zhang et al findings . In contrary, a study carried out on Tunisian population denied any correlation between rs4588 variant and bronchial asthma . Another case‐control study carried out among 6‐year‐old Hispanic children showed that rs4588 and rs7041 GC variants are significant determinants of asthma risk in children …”
Section: Discussionsupporting
confidence: 92%
“…In addition, another study done on Chinese population showed that there is a significant correlation of rs7041 GC variant and development of childhood bronchial asthma where G allele confers more risk of asthma occurrence . On the other hand, Lahmar et al found that different genotype frequencies of GC rs7041 polymorphism did not have significant difference among the study groups. Lahmar study concluded that GC gene variants are not associated with adult bronchial asthma occurrence.…”
Section: Discussionmentioning
confidence: 97%
“…Our study included the rs3782130, rs4646536, rs703842 and rs10877012 polymorphisms in the CYP27B1 gene, which were not associated with the susceptibility to asthma. In line with our findings, a study in a Caucasian population (n = 154 cases/154 controls), mentioned above, found no statistically significant association between CYP27B1 rs108777012 and the risk of asthma [ 61 ]. Moreover, a systematic review showed that the rs4646536 and rs703842 polymorphisms are not related to the risk of developing asthma [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the presence of CYP2R1 rs10741657 was not related to a higher risk of suffering from asthma. Similarly, previous studies conducted in a Caucasian population (n = 154 cases/154 controls) and a Caucasian pediatric population (n = 1386 cases/1305 controls) did not observe any association between this SNP and the susceptibility to asthma [ 49 , 61 ].…”
Section: Discussionsupporting
confidence: 65%
“…,除具有调节钙 磷代谢的经典功能外,在细胞增殖、抗感染、炎症、免疫调 节等方面的作用日益受到研究者的关注 [2] [7] 。 1.3 单核苷酸多态性 遗传变异是个体差异与疾病发生发展的分子基础 [8] ,单 核苷酸多态性是最普遍的遗传变异, 作为第三代遗传标志物, 在诊断基因与疾病之间的关系时更具丰富的动态性和相对稳 定的遗传性 [9] 。 1.4 VD 对呼吸系统健康的作用 呼吸系统疾病主要包括支气管哮喘、慢性阻塞性肺部疾 病、肺结核、急性上呼吸道感染及肺炎等疾病 [10] ,宋航等研 究表明 VD 可减轻小儿喘息性疾病 [11] ;黄涛等研究表明 VD 可能影响肺结核患者预后进程 [12] ;王青青等研究表明补充维 生素 D 可以改善重度吸烟伴维生素 D 缺乏 COPD 男性患者的 肺功能及生活质量,减少急性加重次数 [13] [14] 。李飞等在中国北 方汉族人群进行了类似的研究,也并未发现其与支气管哮喘 的相关性 [15] 。猜测其可能原因是 rs12794714 位点 (C>T)进 行了同义突变,但没有改变其编码的氨基酸序列,未发生结 构和功能上的变化。周晓婷等也进行了同类型研究,得到相 反的结果,结果表明 CYP2R1 基因多态性与支气管哮喘具有 一定的关联性,维生素 D 代谢功能的异常可能影响了支气管 哮喘的发生 [16] 。Zhang Y 等人的研究表明 CYP27B1 基因中 的 rs4646536 与汉族儿童中支气管哮喘的发生发展有明显的 关联性,该位点的表达与支气管哮喘风险增加呈正相关 [17] 。 Oussama L 等人对突尼斯成人支气管哮喘人群做同类型不同 国家人群的研究表明该基因的 rs10877012 中 TT 基因型在女 性支气管哮喘人群中高于男性支气管哮喘人群且该位点的表 达在支气管哮喘的发生发展起到重要作用 [18] 。但于美丽等研 究表明 CYP27B1 基因中的 rs10877012 在儿童支气管哮喘中 可能因 G/T 突变而与支气管哮喘没有显著的相关性 [19] 。由 [20] 。Zella LA 等 人研究发现,GC 基因敲除,可以降低人体血清中 25-(OH)D 含量 [21] 。同时有研究发现支气管哮喘患者肺的功能状态与血 清 25-(OH)D 含量成正相关 [22] [26] ,有 研究表明,可通过补充 VD 从而改善慢阻肺 [27][28][29] 。David AJ 等人在英国伦敦慢阻肺人群进行抽血样调查研究发现 CY-P2R1 基因与慢阻肺无相关性,维生素 D 途径的遗传变异与 维生素 D 的状态或 COPD 的严重程度无关 [30] 。Mathyssen C [31] 。通过查阅大量的文献,未查询到 [32] 。且 Jun Fei 等发现 COPD 患者血清 25(OH)D 水平明显低于对照组 [33] 。以 [34] 。Asadollah Mohammadi 等对伊朗肺结核人群的研 究表明 VDR 基因中的 rs7975232、rs1544410 位点基因型分布 与肺结核病风险无明显的相关性,但其 rs7975232、rs1544410 的多态性可能对欧洲人群的肺结核起到一定的保护作用 [35] 。 Shih-Wei Lee 等对台湾汉族人群 VDBP 基因中的 rs7041 与肺 结核易感性的相关研究表明,Gc1F 携带者和肺结核有一定的 关联性 [36] 。其中,在王喜等对新疆哈萨克人群结核病易感基 因的研究中心表明,VDR 基因中的 rs731236 中,T 等位基因 大多是肺结核病患者共同存在的基因,而 t 等位基因大多为 保护人群免受结核杆菌侵扰的保护基因 [37] 。在对伊朗和云南 人群肺结核患者进行的一项对于 rs731236 的研究中显示肺结 核患者中"tt"基因型的频率比较低。由以上看出,维生素 D 相关基因位点的多态性与肺结核所涉及的耐药性可能存在一 定的关联性 [35,38] [39] 。田慧琴等通过对江苏和安徽 地区无血缘关系的汉族人群进行分析发现 CYP27B1 基因的 SNP 位点 rs10877012 与鼻腔感染的易感性均未发现有统计学 关联…”
Section: 维生素 D 代谢通路基因单核苷酸多态性与呼吸系统疾病的 研究进展unclassified